Investing in acute health services: is it time to change the paradigm? - Kerr, R.; Hendrie, Delia; Moorin, Rachael (CSIRO Publishing, 2014)
Objective: Capital is an essential enabler of contemporary public hospital services funding hospital buildings, medical equipment, information technology and communications. Capital investment is best understood within the context of the services it is designed and funded to facilitate. The aim of the present study was to explore the information on capital investment in Australian public hospitals and the relationship between investment and acute care service delivery in the context of efficient pricing for hospital services. Methods: This paper examines the investment in Australian public hospitals relative to the growth in recurrent hospital costs since 2000–01 drawing from the available data, the grey literature and the reports of six major reviews of hospital services in Australia since 2004. Results. Although the average annual capital investment over the decade from 2000–01 represents 7.1% of recurrent expenditure on hospitals, the most recent estimate of the cost of capital consumed delivering services is 9% per annum. Five of six major inquiries into health care delivery required increased capital funding to bring clinical service delivery to an acceptable standard. The sixth inquiry lamented the quality of information on capital for public hospitals. In 2012–13, capital investment was equivalent to 6.2% of recurrent expenditure, 31% lower than the cost of capital consumed in that year.Conclusions: Capital is a vital enabler of hospital service delivery and innovation, but there is a poor alignment between the available information on the capital investment in public hospitals and contemporary clinical requirements. The policy to have capital included in activity-based payments for hospital services necessitates an accurate value for capital at the diagnosis-related group (DRG) level relevant to contemporary clinical care, rather than the replacement value of the asset stock.